KNOWLEDGE AND ATTITUDES OF PREGNANT MOTHERS TOWARDS THE USE OF FOLIC ACID DURING ANTENATAL AT ENTEBBE REGIONAL REFERRAL HOSPITAL, WAKISO DISTRICT: A DESCRIPTIVE CROSS-SECTIONAL STUDY. - ATAYO, HABIB; Nansereko, Hasifa (Student's Journal of Health Research Africa, 2023)
Background: In Uganda, the uptake of folic acid during pregnancy stands at 3.1% among all pregnant women which has led to an estimated 1400 children with spinal bifida annually. The purpose of this study was to assess the knowledge and attitudes of pregnant mothers towards the use of folic acid during antenatal at Entebbe Regional Referral Hospital, Wakiso district. Methodology: A descriptive and cross-sectional study design that employed quantitative data collection methods was used. A sample size of 30 respondents was selected using a simple random sampling method and responded to a structured questionnaire. Data was analyzed using Microsoft Excel Programs that presented it in the form of frequency tables, pie charts, and graphs. Results: The study results on knowledge revealed that 71.4% had received information about folic acid from health workers, 56.7% did not know the recommended time of starting folic acid, 83.3% knew that they should take one tablet daily and 53.3% knew anemia as a danger of not taking folic acid. Regarding attitude; 43.3% believed that folic acid should not be taken throughout pregnancy, 66.7% disagreed that folic acid can be taken without a prescription, and 76.7% did not feel comfortable taking folic acid during pregnancy. Conclusion: The study concluded that mothers were moderately knowledgeable about folic acid use during pregnancy although they had negative attitudes. Recommendation: It is recommended that health education about folic acid use should be strengthened through the media and at the health facility which will aid in improving mothers’ knowledge and attitudes.